Genetics of insulin resistance in polycystic ovary syndrome. Issue 4 (July 2015) - Obermayer-Pietsch, Barbara; Trummer, Christian; Schwetz, Verena; Schweighofer, Natascha; Pieber, Thomas
Abstract : Purpose of review: Polycystic ovary syndrome (PCOS) is a very common endocrine disease in women all over the world. A variety of symptoms such as hirsutism and hyperandrogenism, irregular menstrual cycles and anovulatory infertility together with metabolic dysfunction, insulin resistance, and type 2 diabetes mellitus in lean and obese individuals and the development of consecutive diseases are key problems in this heterogeneous syndrome. Recent findings: Disease-modifying and potentially disease-causing candidate genes are described. A number of genetic associations have been investigated, whereby genes related to normal-weight insulin resistance and chronic inflammation are of central interest for PCOS pathomechanisms. New insights in the pharmacogenetics of PCOS might help to individualize therapeutic options. Summary: Enormous progress has been made in the genetics of insulin resistance in PCOS. However, because of the individual heterogeneity of PCOS and the lack of evident functional studies, the syndrome is only partly understood to date. Large studies on selected phenotypes and therapy aspects are ongoing.